Desempenho de cultivares de girassol em função da adubação fosfatada em duas safras agrícolas - Soares, Enielson Bezerra (2018)
The sunflower is an oleaginosa of great world importance, whose attributes it potentiates for enormous economic use, standing out the production of the oil, widely used in human food. The choice of cultivars, associated with the proper management of the fertilization, is one of the main components of the production system so that the crop can express the maximum productive performance. However, more detailed informations about the crop nutrition must be obtained. Phosphorus is one of the most limiting nutrients in sunflower development, as it is responsible for important metabolism and nutrition functions of the crop. Therefore, the objective of this work was to evaluate sunflower cultivars in the northeastern semiarid region as a function of doses of phosphate fertilization in two agricultural crops. Two experiments were carried out in 2016 and 2017 at the Rafael Fernandes Experimental Farm, belonging to UFERSA, in Mossoró, RN. The experimental design was in a randomized complete block with four replicates in subdivided plots, where in the plots five Phosphorus doses (0; 50; 100; 150 and 200 kg.ha-1 P2O5) were allocated, and in the subplots three sunflower cultivars (Aguará 06, Altis 99 and Embrapa 122 V2000). The variables evaluated were: P content in the diagnostic leaf, plant height, plant stem diameter, leaf diameter, number of leaves, leaf area, total dry mass, P accumulation and export, number of grains per chapter, productivity maximum efficiency of P, agronomic efficiency, oil content and yield. Phosphorus doses increased the agronomic production components (P content in the leaf, yield of achenes and yield of oil). The dose that provided the best performance of sunflower varied for the different cultivars, in a range between 115 to 123 kg ha-1 of P2O5 in the 2016 agricultural crop and 133 to 188 kg ha-1 P2O5 in the 2017 harvest. The cultivar Aguará 06 reached higher productivity of achenes and oil, among the cultivars analyzed in the agricultural crops.